Approximate Analytic Solution for the Compression and Torsion Process in the Split Hopkinson Pressure Bar - J.Z. Malinowski (Engineering Transactions, 1991)
Simplified analysis of the process of dynamical compression and torsion in the system of the Split Hopkinson Pressure Bar (SHPB) is presented. Bilinear relation of stress to strain σ(ε), for the specimen material and time-independence of the incident pulse σ3(t) = const has been assumed in the solution. In the compression process the effect of friction between the specimen and the rods has been taken into account. As a result of the analysis, the possibility of estimation the time-dependence of the reflected and transmitted pulses in Hopkinson bars and of the mean stress σ(t) and strain ε(t) in the specimen has been obtained. The relations were used to perform calculations, the results of which have been compared with the results of experimental investigations. Small differences between the calculated and the experimental data have been found.